Measuring the Usability of the KPOP’s Application at the South Sumatra Provincial Library Service Using the System Usability Scale Method - Julianti, Eliza; Megawaty, Megawaty (SEULANGA SYSTEM PUBLISHER, 2024)
Current technological developments are very influential in helping work in an agency with the presence of technology able to provide convenience for the community, especially for library service users. KPOP’s is an application in the South Sumatra provincial library to assist visitors in collecting member data and information. The information system in the application needs to be known in measuring the extent to which the KPOP’s application system can be used by users in terms of learnability, efficiency, memorability, errors, and satisfaction. The instrument used in this research is the SUS (system usability scale) method, where this method has 10 statements by distributing questionnaires to 100 respondents. The final results of this research obtained an average score of 69.45, categorized as Marginal High, the grade scale was at grade D, and the adjective ratings were OK, which was almost close to good in terms of use, so the KPOP’s application for the South Sumatra provincial library could be said to be effective in its use.